2011
DOI: 10.1123/jtpe.30.4.410
|View full text |Cite
|
Sign up to set email alerts
|

Social Goals in Urban Physical Education: Relationships with Effort and Disruptive Behavior

Abstract: This study investigated the relationships among four distinct types of social goals, effort, and disruptive behavior in urban physical education. Social responsibility, affiliation, recognition, status goals, along with effort and disruptive behavior in physical education were reported by high school physical education students (N = 314) from three urban schools. Findings from correlation and structural equation modeling analyses revealed that social responsibility goals had a positive relationship with effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
1
23
0
3
Order By: Relevance
“…Some researchers have found that teacher interactions that support students’ personal and social responsibility and accountability are associated with fewer disruptions, increased participation, and greater enjoyment of PE (Balderson & Sharpe, 2005; Garn, McCaughtry, Shen, Martin, & Fahlman, 2011; Li, Wright, Rukavina, & Pickering, 2008). In an effort to support active participation and to limit off-task activities, some teachers offer games over skills-based activities because students might enjoy games more than repetitive skill learning.…”
Section: Enhance Participation By Communicating Relevance Creating Amentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have found that teacher interactions that support students’ personal and social responsibility and accountability are associated with fewer disruptions, increased participation, and greater enjoyment of PE (Balderson & Sharpe, 2005; Garn, McCaughtry, Shen, Martin, & Fahlman, 2011; Li, Wright, Rukavina, & Pickering, 2008). In an effort to support active participation and to limit off-task activities, some teachers offer games over skills-based activities because students might enjoy games more than repetitive skill learning.…”
Section: Enhance Participation By Communicating Relevance Creating Amentioning
confidence: 99%
“…In an effort to support active participation and to limit off-task activities, some teachers offer games over skills-based activities because students might enjoy games more than repetitive skill learning. However, students who seek attention from peers may see large-sided games as an opportunity to showcase disruptive behavior for a ready audience (Garn et al, 2011; Rovegno, 2008). Reducing the visibility of any one child’s performance or skill via small-sided games or activities may reduce some disruptions when students feel less on display (Garn et al, 2011).…”
Section: Enhance Participation By Communicating Relevance Creating Amentioning
confidence: 99%
See 1 more Smart Citation
“…Como segundo elemento clave a analizar del modelo testado, en consonancia con los postulados del modelo jerárquico de Vallerand (1997;, los resultados mostraron que la percepción de satisfacción de los mediadores psicológicos predecían estados motivacionales autodeterminados, coincidiendo con los hallazgos obtenidos en otros trabajos (Baena-Extremera, Gómez-López, Granero-Gallegos, & Martínez-Molina, 2016;Garn et al, 2011). Parece que alumnos responsables y que perciben se perciben autónomos en la práctica (posibilidad de elección), competentes (capaces) y se sienten bien relacionados en la práctica, además de valorados por los demás, generan estados de motivación más autodeterminada en las clases de Educación Física a nivel contextual (Belando et al, 2015;Moreno-Murcia et al, 2012;Méndez-Giménez et al, 2012).…”
Section: Discussionunclassified
“…El clima de responsabilidad se relacionaría positivamente con la motivación intrínseca del estudiante hacia una actividad determinada (Belando et al, 2015;Moreno-Murcia, Huéscar, & Cervelló, 2012). Así, estaríamos ante un clima condicionado por las razones sociales que mueven a los estudiantes hacia la acción de una actividad, denominadas "metas sociales" (Urdan & Maehr, 1995) y que han sido estudiadas en otros trabajos de investigación en Educación Física (Garn, McCaughtry, Shen, Martin, & Fahlman, 2011). Entre las diferentes metas sociales, Guan et al (2006) consideran la meta de responsabilidad como una de las más importantes en Educación Física, la cual, reflejaría el deseo de respetar las reglas sociales y el rol establecido (Wentzel, 1991).…”
Section: Introductionunclassified